Diversity of the Qur’anic discourse for the wives of the Prophet (peace be upon him) “The Efk Incident” as a model - Awaz Agha Hussein (Zanco Journal of Humanity Sciences)
Diversity of the Qur’anic discourse for the wives of the Prophet (peace be upon him) “The Efk Incident” as a model There is no doubt that the (Qur'anic discourse) is one of the best speeches in terms of the sweetness of its words, the eloquence of its text, the accuracy of its systems and composition, the eloquence of its expressions, and that Women in general and the husbands of the Prophet (peace be upon him) have received a share and a wealth of (Qur'anic stories) and speeches, this is a study on "The diversity of the methods of Qur'anic discourse of the wives of the Prophet (peace be upon him) the Efk Incident as a model", with the aim of identifying the language and quality of the letters contained in the ten Surahs in " Al-Nour Surah", which came down in the innocence of our mother Aisha (May God rest her soul), in a linguistic study to show the semantic dimensions provided by lexical, acoustic, drainage, grammatical and rhetorical analysis of these ten surahs.